1992
DOI: 10.3354/meps083063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic cadmium exposures on growth of larvae of an Hawaiian bivalve, Isognomon californicum

Abstract: Young bivalve larvae (3 d old) were exposed to environmentally realistic concentrations of cadmium (2, 10, 20, and 50 pg 1 under static exposure conditions for 28 d, a peilod that spans most of thelr larval lifespan The effects on growth werc evaluated in terms of both size and weight paiameters Cd effects on size growth (length and height) were signlficantly different, but subtle, mostly characterized by a slow gradual decllne, but remaining at 2 80 % of control sizes However the effects of Cd on weight (tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…No data were obtained on changes in shell dimensions for larvae and postlarvae exposed to TBT; however, Ringwood (1992) found that cadmium has no effect on shell lengthshell width relations for larvae of the bivalve Isognomon californicum. In the present study the postlarvae in 1150 ng Sn liter\ have a different shell length-shell width relation compared with postlarvae in the other TBT concentrations.…”
Section: Shell Dimensionsmentioning
confidence: 69%
“…No data were obtained on changes in shell dimensions for larvae and postlarvae exposed to TBT; however, Ringwood (1992) found that cadmium has no effect on shell lengthshell width relations for larvae of the bivalve Isognomon californicum. In the present study the postlarvae in 1150 ng Sn liter\ have a different shell length-shell width relation compared with postlarvae in the other TBT concentrations.…”
Section: Shell Dimensionsmentioning
confidence: 69%
“…The precise effect of this proposed genetic component to embryo copper resistance is not yet known. Although veliger larvae may be capable of producing metallothioneins in response to metal stress (Roesijadi et al 1982, Ringwood 1992, metallothionein induction in the embryo is unlikely to be possible before activation of the zygotic genome at gastrulation. Metallothionein-like proteins have, however, been found in unfertilised sea-urchin eggs (Ohtake et al 1983); the greater resistance of Westerschelde mussel embryos may be a result of inheritance of maternal metallothioneins.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium is toxic and derives from the natural reservoirs, production activities (Foulkes, 1986;EPA, 2007), and participates in both toxicological and ecotoxicological risks (Waisberg et al, 2003 andWHO, 1992). The natural level of cadmium in fresh water is 0.1 to 10 μg/l, while in discharged water can fluctuate from 50 μg/l to 10,000,000 μg/l due to the anthropogenic processes (Singhal and Abusaria, 1990;Ringwood, 1992).…”
mentioning
confidence: 99%